Pre-particle filtration and moisture control by efficient purging in various inlet and outlet of a 450 mm wafer front-opening unified pod - Chiu, Bill; Hu, Shih-Cheng; Shiue, Angus; Shiue, Yu-Yun; Huang, Zhe-Yu (International Journal of Engineering and Technology, 2015)
The trend toward narrower line width in semiconductor manufacturing has made contamination control more and more important. The presence of moisture in wafer containers, such as front opening unified pods (FOUP), can lead to the native oxide residues growth, metal corrosion, and thin film cracking on wafer surfaces. Accordingly, decreasing contamination methods and improving factory efficiency are continuously researched. Single or multi-layer particulate shields on top of wafers in FOUPs may be used to prevent pollutant accumulation. In addition, point-of-use (POU) filtration may also been used to control particle contamination in FOUPs during wafer transformation and storage. The demand for stricter filtration led to the usage of 0.10 and 0.20 Âµm membranes to control the contamination. However, with the introduction of finer membranes end users may have concerns about deleterious remainders on wafers from undergoing filtration. There are a total of 25 pieces of wafers in the FOUP and the arrangement is from the bottom (wafer No. 1) to the top (wafer No. 25) with arising manner. Purging FOUPs to expel moisture vapors with Clean Dry Air (CDA) is one of the most popular methods. There was no previous research for investigating the purge performance on new-generation 450mm FOUPs. This research aims to study main factors influencing the performance of the purge system on 450mm FOUPs, including moisture concentration, CDA flow rate, and filter pressure.